The Influence of EFL Apprehension in Speaking Performance - Hawraa Hashim Hameed; Amaal Eimad Jawad (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The influence of EFL apprehension on speaking performance is a significant area of study in language learning. Empirical studies reveal that anxiety among EFL students is influenced by variables such as communication anxiety, fear of receiving a poor grade, and low self-esteem. during speaking activities. Speech anxiety among ESL/EFL learners can impact their oral communication skills negatively, leading to avoidance and withdrawal from speaking activities in the classroom. Language anxiety, specifically related to speaking, can hinder students' willingness to engage in foreign language acquisition and affect their speaking performance negatively .Research have indicated a connection between EFL students' oral communication anxiety and communication proficiency,highlighting the importance of addressing anxiety to enhance language proficiency.